Quantum dot bead-based immunochromatographic assay for the quantitative detection of triazophos. Issue 1 (1st January 2019) - Wu, Qin; Wu, Peiman; Duan, Hong; Liu, Beibei; Shao, Yanna; Li, Pan; Zhang, Cunzheng; Xiong, Yonghua
ABSTRACT: In this study, a quantum dot (QD) bead -based immunochromatographic assay (QB-ICA) was developed for the rapid, sensitive, and quantitative detection of triazophos. QBs with about 640 times brighter luminescence than the corresponding QDs were used as signal-amplified ICA probes. Under optimum conditions, QB-ICA showed a good dynamic linear detection for triazophos at 0.49–250 ng/mL with a half-maximal inhibitory concentration of 6.97 ng/mL. The average recoveries of intra- and inter assays for triazophos-spiked rice samples ranged from 80.91% to 107.00% with the coefficients of variation below 10%, indicating that QB-ICA had an acceptable accuracy for triazophos detection. The triazophos spiked samples were also detected through gas chromatography, and no significant difference (P > 0.05) was found between the two methods. In summary, the proposed QB-ICA system provided a novel platform for the rapid, sensitive, and quantitative detection of triazophos or other pesticides in food materials.